Assessment of FSAE Car’s Rear Suspension Arms for Bump Force - Muhammad Izzat Nor, Ma'arof; Tan, G.K.H.; Lim, K.H.; G.T., Chala (INTI International University, 2022)
The aim of this study was to design a new upper and lower suspension arm for INTI International University’s Formula Society of Automotive Engineers (FSAE) car with the purpose of off-road usage. The new suspension arm was designed in accordance to regulations of an intercollegiate design competition, BAJA Society of Automotive Engineers (Baja SAE). The material selected for the suspension arms were the 4130-alloy steel. The specifications of the new suspension arms were determined by the size of the bush, inner diameter of 20mm and the position of the mounting on the existing INTI International University’s FSAE car. The study had focused solely on the overall structural strength of the upper and lower suspension arms for off-road usage. The 3D models of the arms were developed using Computer-Aided Design (CAD) via SpaceClaim software. Finite element analysis (FEA) via ANSYS Workbench software was used to determine the structural performance of both suspension arms. The FEA carried out on the designs was bump-force assessment where the vehicle would have jumped and landed on one wheel. For the upper suspension arm, the Maximum Equivalent (von-Mises) Stress (MPa), Maximum Total Deformation (mm) and Minimum Safety Factor were 340.39MPa, 0.42155mm and 1.3514 respectively. Whereas, the lower suspension arm recorded the value of 55.124MPa, 0.12918mm and 8.3448 respectively. These results indicated that the with respect to the design and in using the 4130-alloy steel, both suspension arms will not yield as the Equivalent (von-Mises) Stress value is under the yield limit of 460MPa. The safety factor of the respective designs was also above 1, thus, the safety aspect is indeed ensured for bump force. Nonetheless, the lower suspension arm could be rated as over-designed in accordance to the Safety Factor. Thus, further optimization could be made with respect to the lower arm in future studies.